House on the Pedernales - Kevin Alter; David Heyman (Oz, 1997)
Ex-urban living The arid limestone hills west of Austin have long resisted indiscriminate settlement. Bounded by the Balcones escarpment, these hills are the vestigial trace of the central uplift that once lay at the floor of a great inland sea. Ed. Note: Design for a house in the Pedernales hills, Texas by Kevin Alter of Alterstudio Architecture. Text is by David Hyman.